THE JUVENILE CRIMINAL JUSTICE SYSTEM: THE ROLE AND CONSTRAINTS OF CORRECTIONAL INSTITUTIONS IN PROVIDING GUIDANCE - Kamaruddin, Ainuddin (Faculty of Law Universitas 17 Augustus 1945 Cirebon, 2023)
State Detention Centers (Rutan) serve as a place of correction for detainees and guidance for prisoners, including children involved in criminal offenses. However, children who have completed their sentence often face negative stigma from society, which can reduce their self-confidence. This study aims to understand the development system of juvenile inmates in Cirebon City Class I Detention Center after the implementation of Law No. 11/2012 on Juvenile Justice System, as well as assess the fulfillment of their rights. The research methodology involves field research with direct observation of the coaching system in the detention center. Primary data was collected to provide a comprehensive understanding of juvenile criminal cases. Data was collected through desk research and analyzed descriptively. The results showed that the coaching in Cirebon City Class I Detention Center includes mental development, legal awareness, and independence. This coaching process is in accordance with the mandate of Law Number 11 of 2012 and has been implemented properly, ensuring the fulfillment of the rights of correctional students. In conclusion, the coaching implemented is effective in supporting the rehabilitation and reintegration of children into society, although social challenges still exist. This research emphasizes the importance of continued support from the community to reduce stigma and support children's better future.